2017
DOI: 10.3389/fmicb.2017.02174
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of Growth Phase on the Surface-Layer Associated Proteome of Lactobacillus acidophilus Using Quantitative Proteomics

Abstract: Bacterial surface-layers (S-layers) are semi-porous crystalline arrays that self-assemble to form the outermost layer of some cell envelopes. S-layers have been shown to act as scaffolding structures for the display of auxiliary proteins externally. These S-layer associated proteins have recently gained attention in probiotics due to their direct physical contact with the intestinal mucosa and potential role in cell proliferation, adhesion, and immunomodulation. A number of studies have attempted to catalog th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 48 publications
1
37
0
Order By: Relevance
“…Adhesion of probiotics to host cells is mediated by extracellular polysaccharides and surface layer proteins . The expression of these surface components is regulated by environmental conditions, thus affecting their hydrophobic properties and adhesion efficiency . Furthermore, certain adhesins of lactobacilli are proteases‐sensitive, whereas others are resistant, suggesting that the adhesive properties of probiotics may be altered by P. gingivalis proteolytic activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adhesion of probiotics to host cells is mediated by extracellular polysaccharides and surface layer proteins . The expression of these surface components is regulated by environmental conditions, thus affecting their hydrophobic properties and adhesion efficiency . Furthermore, certain adhesins of lactobacilli are proteases‐sensitive, whereas others are resistant, suggesting that the adhesive properties of probiotics may be altered by P. gingivalis proteolytic activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, our in vitro data suggested that P. gingivalis colonized sites may be more susceptible to colonization by these organisms. Therefore, further experiments are required to reveal how the interactions between probiotic strains, pathogens, and host cells can affect their phenotypes at the proteomic level and the immunological response in complex biofilms …”
Section: Discussionmentioning
confidence: 99%
“…In addition to surface proteins, salt stress also triggered the upregulation of a previously characterized bile-inducible operon encoding a two-component regulatory system (Pfeiler et al, 2007). This system includes two-component response regulator, LBA1431, which possess an OmpR/PhoBtype DNA-binding domain (Pfeiler et al, 2007) and putative SLAP LBA1426 (Klotz et al, 2017). Interestingly, this cluster of genes was not induced in the salt-stressed parent strain.…”
Section: Discussionmentioning
confidence: 99%
“…To complement these results, COGs were assigned using the EggNOG Database (Huerta-Cepas et al, 2016; Figure 7B). Additionally, a previously curated list of the most abundant log phase SLAPs (Klotz et al, 2017), and corresponding fold change, is detailed in Table 2. In MRS, the absence of igdA triggered the significant upregulation of 44 genes, while none were downregulated (Figure 7A, left).…”
Section: Transcriptomic Analysis Of Igda Reveals Upregulation Of Multmentioning
confidence: 99%
See 1 more Smart Citation